Synthesis of 4-Methoxybiphenyl Using Pd-Containing Catalysts Based on Polymeric Matrix of Functionalized Hypercrosslinked Polystyrene - Linda Nikoshvili; Nadezhda Nemygina; Alexey Bykov; Alexander Sidorov; Valentina Matveeva; Irina Tyamina; Mikhail Sulman; Esther Sulman; Barry Stein (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2015)
This paper describes synthesis of Pd-containing catalysts of Suzuki cross-coupling based on amino-functionalized hypercrosslinked polystyrene. The investigation of the influence of a palladium concen-tration, solvent composition, temperature, type and concentration of base, and a type of a gas phase was carried out. It was shown that the catalyst developed allows achieving conversion of 4-bromoanisole higher than 98% for less than 1 h at mild reaction conditions and in the absence of a phase transfer agent. Catalyst reduction was found to result in formation of small Pd nanoparticles (about 3 nm in diameter) and a large number of Pd clusters, which are highly active in Suzuki-Miyaura cross-coupling (conversion of 4-bromoanisole reached 90.2% for 3 h). Copyright © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).